“A GROUP OF ME’S”: Learning Through Group Process for People Living with Multiple Sclerosis - Katharine Preissner; Lisa M. Baumgartner (Adult Education Research Conference, 2014)
The purpose of this study was to understand the learning process that took place during a group program for people with fatigue from multiple sclerosis (MS). Group process, acceptance, and self-compassion supported learning. Several types of learning were present. Findings have implications for health educators of people with chronic illness.